THERMAL PERFORMANCE OF AL2O3-H2O FLOW IN PIPES: A SIMULATION OF DOUBLE TWISTING TAPE WITH AND WITHOUT W-CUTTING - Intisar Rasheed Saleh (Journals Park Publishing, 2025)
This work predicts transfer of heat and drop in pressure of a fluid by simulated a flow in a pipe that has been installed employing double twisted tapes with two cases: with and without cutting. Where two tested fluid that flowing (H2O and Al2O3-H2O). The tests were conducted by applying Re number as a measure of the fluid's velocities, which range from 10000 to 35000. The impact of the presence of the cutting in twisting- tapes and the impact of nanoparticles on improving performance and heat transfer were tested. At the same time, it was determined whether the presence of the pipe with double twisting-tapes has a significant effect on its addition in the presence or absence of nanoparticles. As for the findings of the testing, the pipe with double-twisting tapes with nanofluid flow case expresses a transfer’s heat more effectively than the smooth case; where when using nanoparticles in a pipe with double twisting-tape (φ = 0.02, 0.04, and0.06) at Re=10,000, the performance exceeds 1.74 at φ =0.06 for the case of w-cutting tapes. This indicates that, from the perspective of fluids and heating that transfer, employing a pipe with double twisting tape with cutting and adding nanoparticles is acceptable. As for friction factor values, φ = 0.06 case gives the higher amount of friction factor for all the velocities and for the two cases specially at w-cutting twisted tapes case.
Keywords: Twisted tape, w-cutting turbulent flow, thermal performance, nanofluid.